A new species of Goeppertia (Marantaceae) from the northeast Brazil and an identification key for species from the state of Sergipe - Saka, Mariana N.; Lombardi, Julio A. (Phytotaxa, 2014)
Marantaceae is a family with approximately 550 species distributed throughout the tropics, with the exception of Australia (Andersson 2003). Calathea Meyer (1818: 6) used to be the largest genus in the family, previously including ca. 300 species. After the molecular study on the genus by Borchsenius et al. (2012), which confirmed the genus as polyphyletic, Goeppertia Nees (1831: 337) was resurrected to include all the species (approximately 245) that were not in the former subgenus Calathea Körnicke (1862: 112), the Calathea lanicaulis group (Kennedy et al. 1988) and the synonymized genus Sanblasia Andersson (1984: 21). Goeppertia thus became the most representative genus of Marantaceae, in Brazil represented by ca. 100 species (Braga 2013). It is found chiefly in rainforest habitats at elevations, below 1500m (Kennedy et al. 1988). However, the number of species may yet be underestimated due to unknown diversity of Brazilian species occurring in drier areas.